2017
DOI: 10.1002/jemt.22907
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and effects of metal oxide nanoparticles on microorganisms involved in biological wastewater treatment

Abstract: To clarify the toxicological effects of metal oxide nanoparticles (NPs) on microorganisms with environmental relevance, it is necessary to understand their interactions. In this work, they were studied the effects and the morphological interactions of two metal oxide NPs (ZnO and TiO ) with microorganisms, during aerobic treatment of wastewater. The effects were evaluated according to nutrient removal from wastewater, while morphological interactions were determined by three different techniques such as TEM, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Aggregated NPs can possess different uptake rates, toxic effects, and bioavailability (Misra et al 2012). Attachment of ZnONPs aggregates to the bacterial cells was responsible for significant membrane damage and higher toxicity (Jiang et al 2009;Leung et al 2016;Cervantes-Aviles et al 2017). Thus, the presence of NP aggregates in the test medium along with toxic action of Zn 2+ ions is one of the possible explanations for the higher toxicity of ZnONPs over ZnO nanorods in the present study.…”
Section: Mechanism Of Action Of Zno Nanostructuresmentioning
confidence: 58%
“…Aggregated NPs can possess different uptake rates, toxic effects, and bioavailability (Misra et al 2012). Attachment of ZnONPs aggregates to the bacterial cells was responsible for significant membrane damage and higher toxicity (Jiang et al 2009;Leung et al 2016;Cervantes-Aviles et al 2017). Thus, the presence of NP aggregates in the test medium along with toxic action of Zn 2+ ions is one of the possible explanations for the higher toxicity of ZnONPs over ZnO nanorods in the present study.…”
Section: Mechanism Of Action Of Zno Nanostructuresmentioning
confidence: 58%
“…Then, samples were washed in sodium cacodylate buffer, and postfixed in 1% osmium tetroxide at 4 °C for 24 h. The samples were washed with sodium cacodylate buffer and dehydrated in a graded series of ethanol (50–100%). Finally, samples were embedded in epoxy resin (EPON 812), sectioned with an ultramicrotome to 60–70 nm of thickness, and placed in Cu-based grids for TEM observation (TEM, JEOL JEM 1010) 36 , 37 .…”
Section: Methodsmentioning
confidence: 99%
“…It is also reported that the introduction of high concentration (450-2000 mg/L) ZnO NPs can result in a significant reduction in the removal efficiency of ammonia nitrogen in the activated sludge system [51]. However, as the concentration of ZnO NPs increases, the removal efficiency of ammonia nitrogen does not experience a further decline, and the decrease in ammonia nitrogen removal efficiency remains within the range of 13-14% [51]. Due to the limited research on the BNR exposed to a high concentration of nano-ZnO, the underlying mechanisms behind this phenomenon require further investigation.…”
Section: Effect Of the Nano-zno Concentration On The Bnr Processmentioning
confidence: 99%